Simplifikasi Pembagian Harta Gono-Gini Akibat Perceraian - Mutmainna; Kairuddin Karim; Muhammad Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2021)
Often there is a polemic in the division of common propertyproperty due to divorce has an impact on the occurrence of ongoing turmoil in the family sphere. This research aims to know and understand the process of division of common property due to divorce, and to know and understand the legal considerations of judges in determining or deciding the division of common property due to divorce based on court rulings. This research uses a type of empirical normative research supported by a statute approach and a case study approach. The results showed that the judge's consideration in granting the plaintiff's lawsuit was based in part on evidence and testimony from witnesses.